Effects of swimming and nandrolone decanoate treatment on vas deferens response to norepinephrine - Castor, Lidyane R. G. [UNESP]; Oba, Eunice [UNESP]; Pereira, Oduvaldo C. M. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Aims: To investigate the response to norepinephrine of vas deferens isolated from intact and castrated rats submitted to swimming and/or treated with nandrolone decanoate.Main methods: Intact and castrated male rats were submitted to swimming for 15 days, 1 session per day, 5 days/week and were either treated or not with 7.5 mg/kg of nandrolone decanoate on days 1, 5, 9, and 13 after the beginning of training. Plasma androgen concentration was measured by radioimmunoassay. Vas deferens was isolated and set up for analysis of its contractile capacity in response to norepinephrine.Key findings: In intact rats, nandrolone, training, and training plus nandrolone did not change body mass or vas deferens weight. In castrated rats, the vas deferens wet weight was decreased in both untrained and trained groups. In castrated rats, nandrolone prevented vas deferens atrophy. In intact animals, nandrolone decreased (P<0.05) the androgen level in untrained group, while in castrated rats this treatment partially restored the androgen level. An increased sensitivity (P<0.05) to norepinephrine was observed in vas deferens isolated from intact trained rats, treated or not with nandrolone decanoate, while nandrolone did not alter norepinephrine response in organs from untrained animals. In untrained castrated rats, nandrolone fully restored the sensitivity to norepinephrine in untrained rats, while in trained castrated rats the anabolic steroid only partially restored this response.Significance: The present results indicate that training can increase norepinephrine response of vas deferens in intact rats, while nandrolone decanoate can partially restore the responsiveness to norepinephrine in castrated rats. (C) 2009 Published by Elsevier B.V.
Keywords: Swimming; Vas deferens; Norepinephrine response; Nandrolone decanoate; Rats